Visual Plagiarism In Graphic Design Program - Mohd Noh, Mohd Amin; Amin Nudin, Anith Liyana; Nik Abdullah, Nik Narimah; Shamsudin, Wan Nur Khalisah; Hoo, Fang Jing (2016)
The purpose of this paper is to identify students’ and academicians’ understanding and the contributing factors in visual plagiarism in order to provide appropriate solutions to be applied in the art and design program thus to improve the academic integrity among the university community. This research employed a qualitative research with purpose to investigate the different opinions and the contributed factors related to visual plagiarism in the design assessment among students and academicians. The sample of this research consists of eight students and two academicians from graphic design program in Universiti Teknologi MARA (UiTM) Melaka campus. The credibility and confirmability of qualitative validity has been made to approve the legitimacy of the results (Lincoln & Guba, 1985). This study had discovered that students have different understanding regarding visual plagiarism. The confusion has led to the misuse of visual references from other resources and some of them are not aware that plagiarism is considered as an offence in the academic setting. The contribution factors of wrong decision-making in selection topic, time mismanagement in design progress, and disregard consultation session with academician cause students to commit visual plagiarism. Academician’s unwillingness to convey information to students about visual plagiarism in details for every course in graphic design program contributes to the miscommunication among students in designing artworks. Nevertheless, every academician agreed that visual plagiarism should be taken seriously to curb the situation from deteriorating. The trend of visual plagiarism in design assessment for art and design program is alarming. Academic community should consider any measures to address the issue not only in terms of restrictions and punishments but most importantly to educate students to value people’s ideas and works and to improve academic integrity